Numerical study on the performance and flow characteristic of wind using invelox system / Siti Sarah Ramani @ Abdullah - Siti Sarah, Ramani @ Abdullah (2021)
In recent years, power generated by wind turbine has been gaining a lot of interest because of the growing concerns of climate change. Since power generated by wind turbine is proportional to the rotor size and the cube of the wind’s velocity, wind turbine has grown massive in size. To build these gigantic devices, large amount of capital needs to be invested. The challenge facing in the wind power world is to build an efficient device that minimizes the size and cost and maximizes the power output. A wind power technology that may be able to do this is the ducted wind turbine. A ducted wind turbine uses a ducted system to capture wind and increase its velocity, which enables the wind turbine to generate more electricity. Initially the flow through a simple Invelox was simulated and the results validated with the developer’s results. The developed Invelox model was then analyzed with inclusion of a wind turbine to achieve a wind speed of 11.90 m/s at venturi section giving a speed ratio of 1.72. The performance of Invelox system was analyzed with wind flows from 8 different directions (0˚, 45˚, 60˚, 90˚, 120˚, 135˚, 150˚, 180˚) with respect to turbine axis. It is observed that higher speed ratios are achieved in all case expect 135˚ and 225˚ angles. Highest wind speed ratio of 2.014 is achieved